Pola zonasi ekosistem mangrove di Desa Juanga Kabupaten Pulau Morotai - Kismanto Koroy; Sandra Hi. Muhammad; Nurafni Nurafni; Nurti Boy (Fakultas Perikanan dan Ilmu Kelautan, Universitas Papua, 2020)
ABSTRACTMangroves are one of the most important natural resources in coastal areas. Availability of various types of food that are on ecosystems is already making its presence as a local nursery, where searching for eating and also serve as a regional tourist ecosystem of mangrove. In use as Regional tourist mangrove need to attention the condition of the physical environment and the distribution pattern of zoning. Research is carried out in the month October to November 2019 in the village of Juanga Regency island of Morotai. Data zoning mangrove using the method of the combination is to combine the methods of plots to track transects, to determine the four stations of observation of each respective stations and each station is divided into three zones: zone front, zone of middle and zone back starting from the point of the outermost growth of types of mangrove constituent primary to the point of transition between sea and land. The research results of the study found 5 types of mangroves namely Rhizophora mucronata, Ceriops decandra, Rhizophora apiculata, Xylocarpus granatum and Sonneratia alba. The distribution of zoning patterns in the front zones of station I and the middle zone is dominated by Rhizophora mucronata and Rhizophora apiculata types, the rear zone is dominated by Ceriops decandra. Station II front zone is dominated by Sonneratia alba, middle zone (Rhizophora mucronata), rear zone (Ceriops decandra). At station III the front zone (Rhizophora apiculata), the middle zone and the rear zone (Ceriops decandra) while at station IV the front zone, the middle zone and the rear zone are dominated by the Ceriops decandra type.